RELAÇÃO ENTRE A EDUCAÇÃO PARENTAL E OS ACIDENTES DE TRABALHO - Santarém, Jorge Lucio Basto (2008)
This study examines the safe work as a result of the educational process during the occupational life. The purpose of the text is to demonstrate that people who live safely in familiar and social ambient are more aware and responsible with safety at the professional workplace. It also shows that stressful actions outside the workplace contribute to accidents occurring at work. The issues investigated in this study were: "May parenting styles of education adopted by workers be linked directly or indirectly with absences, incidents or accidents at work?", "Do concerns about loved ones and other domestic situations interfere in the perception of risk at workplace? and Why do we have so much attention on security at work, while at home we neglect, causing loss of time, absences, incidents or accidents at workplace?". For the purposes of the study, we used literature and documentary search, exploratory and descriptive, such as books consulting, journals and web sites, in addition to documentation provided by the company that hosted the fieldwork. The field research took place in Rio de Janeiro and Singapore, by questionnaire, composed by open and closed questions applied to safety management professionals who work in high seas businesses. The results of the research show that we must review the conduct of professionals at home and that simple prevention attitudes related to family education are one of the keys to develop a responsible man, who acts safely in all situations, especially at work. The style of parental education is proposed as an initiative for a responsible action, for a safety work.